Instability Model of a Coal Wall with Large Mining Height under Excavation Unloading Conditions - Lei Li; Feng zhang (Advances in Civil Engineering)
On the basis of the stress field characteristics of surrounding rocks at a coal wall on a working face with a large mining height, the theories of unloading rock mass mechanics and fracture mechanics were used to establish a model of the excavation unloading field effect of the coal wall, and its instability mechanism under the action of unloading stress field was analyzed. Results show that the coal mining process is the unloading process of coal and rock masses, and the stress field of surrounding rocks at the coal wall turns into an unloading stress field that consists of original and unloading stresses. Under the action of unloading stress field, cracks in the coal wall will undergo instability, propagation, and combination in the form of composite-type cracks and will gradually evolve into a wedge structure. The wedge stability is inversely related to roof pressure P0, unloading force T, and intersection angle φ of structural planes. Elevating the wall-supporting force Ph, the initial supporting force of supports on the working face and the cohesion C of coal body can effectively control the occurrence of coal wall caving accidents and contribute to the safe mining of working faces with a large mining height.